Solvent-free protocol for the green synthesis of benzamide analogs of dibenzoazepine - Khan, Maria Aqeel; Batool, Farhana; Khatoon, Asma; Sadiq, Rabia; Rahman, Sher; Basha, Fatima Zehra (European Journal of Chemistry, 2017)
Dibenzoazepine represents an important class of heterocycles, exhibiting potent antidepressant and anticonvulsant activities. Beside, various modifications on this nucleus, amide analogs at N-5 position showed potent antidepressant activities. A previously reported method for the synthesis of benzamide analogs of dibenzoazepine use hazardous and toxic solvents. Herein, we report a new, efficient and solvent-free green method for the synthesis of dibenzoazepine benzamides (6-21).